Creating a Conducive School Learning Environment through Signage and Wayfinding Design - Ismiyati Hanum; Didit Widiatmoko Soewardikoen; Irwan Sudarisman (Smart Society, 2025)
A conducive learning environment is a key determinant of educational success, particularly at the junior secondary school level, where students require not only cognitive stimulation but also physical and emotional support. This study aims to address facility-related challenges at SMPN 1 Warureja, Tegal Regency, where the absence of comfortable rest areas, limited creativity spaces, and inefficient spatial layout have hindered student comfort and engagement. Employing the Design Thinking approach empathize, define, ideate, prototype, and test this research involved observations, in-depth interviews, and student surveys to explore students’ and teachers’ perceptions and identify core user needs. Data analysis revealed a strong demand for child-friendly, inclusive, and participatory spatial designs that support learning motivation and well-being. Based on these insights, a spatial redesign strategy was developed and pilot-tested, showing a significant increase in student comfort and engagement levels. The findings highlight the novelty of integrating Design Thinking as a participatory, context-sensitive method for educational facility planning, which not only empowers users but also aligns designs with local socio-cultural values and sustainability principles. This research offers a replicable model for schools seeking innovative, inclusive, and student-centered solutions to improve learning environments and promote holistic educational outcomes.